Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-1203
|View full text |Cite
|
Sign up to set email alerts
|

Information Bottleneck Based Percussion Instrument Diarization System for Taniavartanam Segments of Carnatic Music Concerts

Abstract: An approach to diarize taniavartanam segments of a Carnatic music concert is proposed in this paper. Information bottleneck (IB) based approach used for speaker diarization is applied for this task. IB system initializes the segments to be clustered uniformly with fixed duration. The issue with diarization of percussion instruments in taniavartanam is that the stroke rate varies highly across the segments. It can double or even quadruple within a short duration, thus leading to variable information rate in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This approach employs a sequence-to-sequence neural network trained on both lexical and acoustic features. Recently, we proposed a varying length segment initialization technique using the stroke onset rate information to diarize percussion instruments in Carnatic music concerts [13]. It is shown that segment length initialization based on stroke rate improves the performance of the percussion instrument diarization system.…”
Section: Approaches To Speaker Diarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach employs a sequence-to-sequence neural network trained on both lexical and acoustic features. Recently, we proposed a varying length segment initialization technique using the stroke onset rate information to diarize percussion instruments in Carnatic music concerts [13]. It is shown that segment length initialization based on stroke rate improves the performance of the percussion instrument diarization system.…”
Section: Approaches To Speaker Diarizationmentioning
confidence: 99%
“…Motivated from [10], [11], and [13], we propose a varying length segment initialization technique to address this problem. [10] focuses on good initialization of clusters.…”
Section: Varying Length Segment Initialization For Ib (Varib) Based D...mentioning
confidence: 99%
See 1 more Smart Citation